'A window to knowledge is a window to the world': socio-aesthetics, ethics and pedagogic migrant youth journeys in crisis-shaped educational settings in Greece. Issue 2 (4th March 2021) - Christou, Anastasia; Michail, Domna
ABSTRACT: This paper explores the processes, tensions, opportunities and constraints that migrant youth in Greek higher educational institutions experience at the present time which are characterised by social crises, economic austerity and political instability. In doing so, we also put forward an agenda of critical and feminist pedagogies in developing inclusive spaces of educational citizenship and social justice. Building on a larger collaborative study on youth and migration, this paper draws on a sample of 130 interviews with women and men second generation migrants who are currently, or have been in the past, university students at various institutions in Greece. Migrant youth expanding on their aspirations and capacities harness a developmental pathway of cosmopolitan pedagogies which alter their circumstances and social possibilities. The paper advances alternative discourses in crafting spaces of anti-oppression in the academy through a feminist lens which will cultivate learning communities of equity, justice and reflexivity.